International Business Management Succeeding in a Culturally Diverse World - Fatehi, Kamal; Choi, Jeongho; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This textbook explores the theoretical and practical aspects of managing international business operations while also dealing with multi-cultural, multi-national and global issues of managing business expansion beyond the domestic market. A second, revised edition of Managing Internationally: Succeeding in a Culturally Diverse World, each chapter contains up-to-date material, in-depth coverage of topics, visual aids (i.e., charts, tables, etc.), and vignettes, making this new edition engaging, visually appealing and easily accessible for students taking International Business Management courses. The contents of this textbook are separated into four parts. Part one offers introductory information on the scope and importance of international business management as well as the social and ethical challenges. Part two covers cultural and behavioral topics. Part three discusses the strategic and operational aspects of international business management. Part four explores human resources and labor relations. To assist students, each chapter starts a preview section which includes an outline of the chapter indicating the important aspects along with a brief description of the major issues. Following the preview is a vignette that encapsulates the crux of the chapter, often presented in an amusing and engaging manner. To further help students focus on key issues, the text includes the list of useful business cases to which students can refer. To assist professors in teaching from this book, ancillary teaching materials such as sample syllabi, slides, tests and answer keys will be available for download. .
Part I: Introduction -- CH 1: The Management of International Business -- CH 2: Socio-Ethical Issues and International Management -- Part II: Cultural and Behavioral -- CH 3: International Management and the Cultural Context -- CH 4: International Communication and Negotiation -- CH 5: Management Leadership and Motivation in an International Context -- Part III: Strategic and Operational -- CH 6: International Environment and Strategy -- CH 7: International Strategic Alliance -- CH 8: Organization of Multinational Operations -- CH 9: Control of International Operations -- CH 10. International Management Information System -- Part IV: Human Resources -- CH 11: International Human Resource Management -- CH 12: International Labor Relations -- Appendix A: Major Leadership Theories -- Appendix B: Major Motivation Theories -- Appendix C: Charter of the United Nations -- List of Cases -- Name Index -- Subject Index.
Keywords: International business enterprises$1 (BCross-cultural studies.s; Leadership; Personnel management; Management information systems; Cross-Cultural Management; Business Strategy/Leadership.; Human Resource Management; Business Information Systems